2019
DOI: 10.1017/s0007114519001508
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin attenuates insulin resistance and hepatic lipid accumulation in a rat model of intra-uterine growth restriction through insulin signalling pathway and sterol regulatory element binding proteins

Abstract: The objective of the present study was to investigate the effect of curcumin on insulin resistance (IR) and hepatic lipid accumulation in intra-uterine growth restriction (IUGR). Rats with a normal birth weight (NBW) or IUGR were fed basic diets (NBW and IUGR groups) or basic diets supplemented with curcumin (NBW-C and IUGR-C groups) from 6 to 12 weeks. Rats in the IUGR group showed higher levels of glucose and homeostasis model assessment for insulin resistance index (HOMA-IR) (P < 0·05) than in the NBW gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Furthermore, in the liver, curcumin diminished total cholesterol, TG, and non-esterified fatty acids (NEFA); increased glycogen concentration and induced the activation of lipolytic enzymes, together with a reduction in IRS-1 and Akt phosphorylation, a decrease in CD36, SREBP-1, and FASN expression, and an increase in PPARα levels. Overall, these data showed that curcumin could improve IR and lipid accumulation in the liver by regulating insulin signaling pathways, and promoting lipolysis and fatty acid oxidation in FGR rats [ 56 ].…”
Section: Role Of Curcumin In Pregnancymentioning
confidence: 99%
“…Furthermore, in the liver, curcumin diminished total cholesterol, TG, and non-esterified fatty acids (NEFA); increased glycogen concentration and induced the activation of lipolytic enzymes, together with a reduction in IRS-1 and Akt phosphorylation, a decrease in CD36, SREBP-1, and FASN expression, and an increase in PPARα levels. Overall, these data showed that curcumin could improve IR and lipid accumulation in the liver by regulating insulin signaling pathways, and promoting lipolysis and fatty acid oxidation in FGR rats [ 56 ].…”
Section: Role Of Curcumin In Pregnancymentioning
confidence: 99%
“…Curcumin (CUR) is the main active component of turmeric and has proved to be effective in preventing obesity, diabetes, and inflammation (Carrera-Quintanar et al, 2018). CUR supplementation is reportedly effective in alleviating hepatic steatosis via modulating lipid metabolism such as cholesterol, TG, and free fatty acid (FFA) concentrations (Ferguson et al, 2018), and improving IR in highfat-diet (HFD)-fed obese rats (Niu et al, 2019). Another study provided new evidence that CUR supplementation significantly shifted the ratio between beneficial and pathogenic microbiota (Feng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the use of herbal medicines to promote glycemic and metabolic homeostasis in pathological conditions such as DM is becoming increasingly popular in the world’s population [ 24 ]. In this context, supplementation with turmeric ( Curcuma longa L.), in different ways, appears to act beneficially on glycemic control; these effects are partly due to an attenuation of insulin resistance and frequently encountered comorbidities in patients with diabetes [ 25 , 26 ]. Some authors suggest that these effects of turmeric are partly due to the high concentrations of curcumin that have antioxidant action [ 27 – 29 ].…”
Section: Introductionmentioning
confidence: 99%